The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1991
DOI: 10.1016/0014-5793(91)80392-g
|View full text |Cite
|
Sign up to set email alerts
|

Activation of protein kinase C by phorbol esters induces DNA synthesis and protein phosphorylations in glomerular mesangial cells

Abstract: The tumor‐promoting phorbol ester 12‐O‐tetradecanoylphorbol 13‐acetate (TPA) is shown to be mitogenic for quiescent glomerular mesangial cells cultured in serum‐free conditions. TPA induces DNA synthesis measured by PH thymidine incorporation in a dose‐dependent manner with an ED10 of 7 ng/ml and an optimal response for 50 ng/ml. The phorbol ester action is potentiated by insulin with an increase of the maximal effect from 232 ± 15% of TPA alone to 393 ± 96% for TPA plus insulin. Down‐regulation of protein kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

1991
1991
2000
2000

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 26 publications
0
8
1
Order By: Relevance
“…For experiments using staurosporine, 5 /g/ml of insulin were added to the incubation medium. As previously reported, insulin alone has no effect by itself but potentiates the effect of TPA and Des-Arg'bradykinin (Issandou and Darbon, 1991). By contrast, we found that insulin did not increase the mitogenic response observed with optimal bFGF concentrations (data not shown).…”
Section: Mitogenesis Assaycontrasting
confidence: 58%
See 3 more Smart Citations
“…For experiments using staurosporine, 5 /g/ml of insulin were added to the incubation medium. As previously reported, insulin alone has no effect by itself but potentiates the effect of TPA and Des-Arg'bradykinin (Issandou and Darbon, 1991). By contrast, we found that insulin did not increase the mitogenic response observed with optimal bFGF concentrations (data not shown).…”
Section: Mitogenesis Assaycontrasting
confidence: 58%
“…Prolonged exposure of cells with phorbol esters is known to down-regulate protein kinase C in mesangial cells (Pfeilshifter, 1989), as well as in other cell lines (Darbon et al, 1987;Rozengurt, 1989,1990). After such a pretreatment, we have previously shown that TPA was unable to trigger DNA synthesis while serum was still effective (Issandou and Darbon, 1991). As shown in Figure 2 (closed circles), a 2-day pretreatment with 320nM TPA did not prevent bFGF from stimulating DNA synthesis.…”
Section: Results Bfgf Is a Potent Mitogen For Mesangial Cellsmentioning
confidence: 84%
See 2 more Smart Citations
“…For example, both the B1 and B2 receptors mediate pain perception (45); both receptors activate phospholipase C in mesangial cells (46); and both receptors stimulate mitogenesis in fibroblasts (36). In addition, the structural similarities of the B1 and B2 receptor agonists suggest that the kinin receptors may be isoforms.…”
Section: Fibrogenesis and Des-argmentioning
confidence: 99%